Factors affecting the implementation of low-level oral questioning in mathematics teaching in primary school - Mahmud, Muhammad Sofwan; Md. Yunus, Aida Suraya; Mohd Ayub, Ahmad Fauzi; Sulaiman, Tajularipin (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The purpose of this study was to identify factors that influence the implementation of low-level oral questioning in mathematics teaching in primary school. This study was a qualitative study using the case study method. Data were collected through partial structural observation, semi-structured interview, document analysis and field notes. Six mathematics teachers from six different primary schools were selected as participants of the study using purposive sampling method. The data were then analyzed using a constant comparative method to identify the patterns and themes that emerged from the data obtained. The study identified that factors of time constraint, heavy workload, extensive coverage of contents, low level student achievement, student engagement, and lack of in-service training contributed to the lack of high level questionings in the mathematics teaching process. These factors need to be addressed so that students' thinking can be enhanced through higher level oral questioning activities during the class.